2016
DOI: 10.4103/2231-0762.175404
|View full text |Cite
|
Sign up to set email alerts
|

Association of yoga practice and serum cortisol levels in chronic periodontitis patients with stress-related anxiety and depression

Abstract: Aim:Reducing the psychosocial stress by various methods can improve overall health, and yoga is now considered as an easily available alternative method. The present cross-sectional pilot study was conducted mainly to find the association of yoga practice with periodontal disease by measuring serum cortisol levels.Materials and Methods:A total of 70 subjects with age range of 35–60 years suffering with chronic periodontitis were divided into group I (with stress), group II (without stress), and group III (prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
2
20
0
1
Order By: Relevance
“…This is in line with previous studies that serum cortisol can be a reference marker of atherosclerosis . Serum cortisol levels are associated with psychological stress . It is suggested by clinical data that chronic psychological stress is associated with the pathogenesis of atherosclerosis .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with previous studies that serum cortisol can be a reference marker of atherosclerosis . Serum cortisol levels are associated with psychological stress . It is suggested by clinical data that chronic psychological stress is associated with the pathogenesis of atherosclerosis .…”
Section: Discussionsupporting
confidence: 92%
“…17 Serum cortisol levels are associated with psychological stress. 18,19 It is suggested by clinical data that chronic psychological stress is associated with the pathogenesis of atherosclerosis. 20,21 The concept is also supported by the animal model study.…”
Section: Discussionmentioning
confidence: 99%
“…This previous study[ 41 ] showed a link between circadian rhythms sleep and cognition. Further, recent previous cross-sectional study[ 42 ] showed that the yoga practice reduces the cortisol levels anxiety and depression. In addition, relaxation induced by diaphragmatic breathing decreases the oxidative stress and cortisol levels.…”
Section: Methodsmentioning
confidence: 99%
“…Yoga has been demonstrated as a curative measure for the modifiable and non-modifiable risk factors of periodontitis [4]. Numerous researchers have proven the positive effect of Sudharshankriya on various systemic and psychological diseases and shown a favorable effect on inflammation [5].…”
Section: Introductionmentioning
confidence: 99%